2022
DOI: 10.1111/all.15569
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulated lipidome of sebum in patients with atopic dermatitis

Abstract: Background: Lipids are the major components of skin barrier, mainly produced by keratinocytes and sebaceous glands. Previous studies on barrier dysfunction of atopic dermatitis (AD) mainly focus on the lipids from keratinocytes, whereas the role of sebaceous gland-derived lipids in AD has long been underrecognized. Methods:The sebum secreted on the skin surface of AD patients was measured using the Delfin Sebum Scale. Sebum was collected using Sebutape patches and subjected for liquid chromatography tandem-mas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 37 publications
2
6
0
Order By: Relevance
“…39 A recent paper has reported dysregulation of sebum production in AD in keeping with aberrant expression of genes regulating lipid biosynthetic pathways, including FA de novo synthesis, elongation and desaturation. 52 While the lipid domains evaluated in previous studies differed from those addressed here, coincident results were obtained on the significant depletion of TGs in AD sebum. Our approach addressed sebum-specific biomarkers, e.g., squalene, sapienate and branched FFAs, indicating compromised early events in the lipid cascade leading to sebaceous end products, including TGs and WEs.…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…39 A recent paper has reported dysregulation of sebum production in AD in keeping with aberrant expression of genes regulating lipid biosynthetic pathways, including FA de novo synthesis, elongation and desaturation. 52 While the lipid domains evaluated in previous studies differed from those addressed here, coincident results were obtained on the significant depletion of TGs in AD sebum. Our approach addressed sebum-specific biomarkers, e.g., squalene, sapienate and branched FFAs, indicating compromised early events in the lipid cascade leading to sebaceous end products, including TGs and WEs.…”
Section: Discussionsupporting
confidence: 54%
“…Expression of enzymes involved in the elongation of FFAs present with different distribution in AD epidermis 39 . A recent paper has reported dysregulation of sebum production in AD in keeping with aberrant expression of genes regulating lipid biosynthetic pathways, including FA de novo synthesis, elongation and desaturation 52 . While the lipid domains evaluated in previous studies differed from those addressed here, coincident results were obtained on the significant depletion of TGs in AD sebum.…”
Section: Discussionsupporting
confidence: 45%
See 1 more Smart Citation
“…Dysbiosis of the skin microbiota and opportunistic bacteria colonization is common in AD ( 163 ). Recent studies found that the opportunistic pathogen S. aureus was shown to cause barrier damage via disruption of the lipid composition, which is crucial for skin barrier integrity and causing inflammation in skin ( 116 , 161 , 164 , 165 ). Interestingly, Stuvel et al .…”
Section: Diseases Associated With Epithelial Barrier Impairmentmentioning
confidence: 99%
“…The role of lipids from sebaceous glands in barrier dysfunction of atopic dermatitis (AD) has been under‐recognized. Yin and colleagues 9 noticed that aberrant lipid metabolism in sebaceous glands was correlated with skin inflammation and barrier dysfunction, and contributed to the pathogenesis of AD. Another group indicated that human CST1 protein suppressed asthma symptoms by protecting the asthmatic bronchial epithelial barrier through inhibiting allergenic protease activity, indicating CST1 as a potential biomarker for asthma control 10 .…”
Section: Figurementioning
confidence: 99%